2022
DOI: 10.3390/nu14020329
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of the Soluble Dietary Fiber from Laminaria japonica and Its Role in the Regulation of Type 2 Diabetes Mice

Abstract: Laminaria japonica is a large marine brown alga that is annually highly productive. However, due to its underutilization, its potential value is substantially wasted. For example, a lot of Laminaria japonica cellulose remains unused during production of algin. The soluble dietary fiber (SDF) was prepared from the byproducts of Laminaria japonica, and its physicochemical properties were explored. SDF exhibits good water-holding, oil-holding, water-absorbing swelling, glucose and cholesterol absorption capacity,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Cholesterol is a crucial nutrient that is both a necessary component of the body’s structure and a building block for generating important compounds. Reports indicate that augmenting the intake of SDF (soluble dietary fiber) will effectively lower cholesterol levels [ 41 ]. Therefore, under the simulated gastric and intestinal conditions of pH 2 and pH 7 for 3 h, the CAC of the samples was measured, as shown in Figure 4 d. At pH 2, YF-SDF has the highest CAC (14.66 ± 0.06 mg/g) ( p < 0.05); at pH 7, BF-SDF has the highest CAC (35.64 ± 0.75 mg/g) ( p < 0.05), followed by LF-SDF and YF-SDF, while there is no significance different between them.…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol is a crucial nutrient that is both a necessary component of the body’s structure and a building block for generating important compounds. Reports indicate that augmenting the intake of SDF (soluble dietary fiber) will effectively lower cholesterol levels [ 41 ]. Therefore, under the simulated gastric and intestinal conditions of pH 2 and pH 7 for 3 h, the CAC of the samples was measured, as shown in Figure 4 d. At pH 2, YF-SDF has the highest CAC (14.66 ± 0.06 mg/g) ( p < 0.05); at pH 7, BF-SDF has the highest CAC (35.64 ± 0.75 mg/g) ( p < 0.05), followed by LF-SDF and YF-SDF, while there is no significance different between them.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to fucoidan and iodine, alginates, polyphenols, and polysaccharides as bioactive nutritional compounds extracted from LJP have been evaluated as solutions for the treatment and prevention of Met-related diseases [ 81 ]. In this review, alginates, polyphenols and polysaccharides have been reported to possess anti-diabetic [ 3 , 10 , 19 , 24 , 33 ], anti-obesity [ 29 , 30 , 31 , 32 , 38 ], antioxidant [ 15 , 34 , 37 ], anti-inflammatory [ 37 , 38 ], and hypolipidemic [ 15 , 33 , 34 , 37 ] effect.…”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, brown seaweed contains various phenolic compounds with anti-inflammatory, antioxidant, and anticarcinogenic properties [ 8 ]. Laminaria species are a vital marine medicinal food source that have biological effects on the human body [ 9 ], wherein Laminaria japonica (LJP) is a rich source of algae, minerals, and dietary fiber as well as a vital source of dietary fiber production [ 10 ]. In Korea, Japan, and China, LJP is cultured as one of the most economically important seaweeds [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fiber (DF), comprising soluble dietary fiber (SDF) and insoluble dietary fiber (IDF), is a nondigestible polysaccharide derived from plants that exhibits strong hydration and adsorption properties and serves a crucial function in the gastrointestinal tract, including maintaining well-balanced gut microbial ecology, increasing fecal volume, adsorbing and quickly excreting excess glucose, lipids, and toxic substances, and reducing the occurrence of cardiovascular disease, stroke, and diabetes ( Gill et al, 2021 ; Makki et al, 2018 ). Recent studies have demonstrated that either SDF or IDF derived from L. japonica could alleviate chronic diseases such as diabetes and obesity in mice by increasing the abundance of beneficial bacteria (e.g., Akkermansia ) and decreasing the abundance of pernicious bacteria (e.g., Staphylococcus ) through fermentation, which produced short-chain fatty acids and lowered the pH ( Wang et al, 2022 ; Zhang et al, 2021 ). Although both SDF and IDF have many health benefits, SDF has shown more positive effects in increasing viscosity, forming gels, and providing better texture and taste and is generally considered more important than IDF ( Chen and Wu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%